The Influence of the Menstrual Cycle in Postdural Puncture Headache. Issue 5 (September 1998) - Echevarria, M.; Caba, F.; Rodriguez, R.
Abstract : Background and Objectives: We performed a preliminary study to analyze the influence of the menstrual cycle on the incidence of postdural puncture headache (PDPH). Methods: One hundred sixty female patients with regular menstrual cycles who received spinal anesthesia were observed. Based on the day within the menstrual cycle that they received the puncture, the patients were classified into period A (perimenstrual) or period B (postmenstrual). The possible relationship among headaches, lifestyle habits, and anesthetic technique, and the presence of PDPH were analyzed, as were the levels of female sex hormones with PDPH in comparison with a control group. Results: Seven cases of PDPH (4.3%) were observed—one within the perimenstrual group and six in the postmenstrual group. No significant differences were observed between the two periods or were there any differences in relating PDPH to the other variables analyzed. Conclusions: According to our results, the menstrual cycle and hormonal levels may not have any influence on the appearance of PDPH in female patients, although a larger series is required to validate these results.